Evaluation of Anthelmintic Activities of Fractions of Acanthus Montanus (Acanthaceae) on Adult Heligmosomoides Bakeri (Nematoda, Heligmosomatidae) - O. Oshadu David; O. Ajanusi Joseph; N. Chiezey Patricia; S. Abubakar Mohammed; N. Patrobas Maryam; Adamu Mathew; Abraham I. Dogo Goni (Journal of Parasite Research, 2021)
Acanthus montanusNees T. Anderson (Acanthaceae) has been employed in folk medicine for treatment of different kinds of ailment, but there is dearth of documented information on its therapeutic activities against parasites. In this study, pulverized Acanthus montanusleaf was subjected to four different extraction techniques. The percentage of yields were 25.58%, 31.42%, 11.58% and 3.00% weight by weight (w/w) of crude ethanol extract (CEE), aqueous (AQ), n-butanol (BUT) and chloroform (CHLO) portions, respectively. All the extracts, excluding the chloroform portion were administered to worm-infested mice per os at dose of 1.2 g/kg, 1.4 g/kg, 1.7 g/kg and 2.0 g/kg each for five days consecutive. Mice were euthanized and the adult worm counted for rates of deparasitization. The aqueous extract did not cause significant deparasitization even at the highest dose of 2.0 g/kg. The CEE caused significant (p<0.05) deparasitization rate of 72.35% at 2.0 g/kg dose. The n-butanol portion caused significant (p<0.05) deparasitization rates at doses between 1.4 mg/kg and 2.0 mg/kg (86.17% and 97.04% respectively) compared to figures from distilled water-treated mice (Control) as well as those from mice treated with the aqueous or crude ethanol portion. The 97.04% deparasitization produced by the 2.0 g/kg dose was not stastistically different (p>0.05) from the 100% deparasitization obtained using albendazole at the manufacturer’s recommended dose of 10 mg/kg. This study has demonstrated that the n-butanol extract of Acanthus montanus leaf has profound anthelmintic activity against experimental Heligmosomoidesbakeri infection in mice. Further phytochemical analysis and evaluation is being advocated in large animals and possibly human subjects.
Keywords: Evaluation